Morphological and mechanical properties of short fibres reinforced hybrid composites for automotive applications. (2022) - Dilip Kumar, K.; Shantharaja, M.; Kumar, Nithin; Manjunatha, G.
Abstract: Polymer systems like epoxies are seldom used in the manufacturing of structures on their own since their mechanical properties are not very high. The matrix system of materials is availed by the process of thermosetting or thermoplastic polymer and the corresponding filler material or reinforcement used are of ceramic, metal, carbon, particulates or fibres. In this work hybrid fibre reinforced epoxy composites are fabricated and tested with the intention of improving the mechanical properties of the composites for use in various applications like automobiles, aerospace, civil engineering, military, motorsports etc. Samples of epoxy composites, reinforced with various combinations of carbon, glass, and nylon fibres have been prepared by varying the amount of one of the fibres, using hand layup technique. This technique involves placing layers of composite fibre in a sequence layup using epoxy matrix and hardener, then subjecting to uniform pressure under room temperature. The composite materials so produced are tested for their mechanical properties according to ASTM standards. With varying fibre contents, a notable variation in mechanical properties was observed. The samples fabricated by combining various quantities of different fibres, exhibited the best mechanical properties. The effect of hybridization and fibre content on the mechanical properties results in improved strength and stiffness for glass fibre and nylon fibre but reduces the impact strength, which can be improved by the addition of nylon fibre.